LAMINAR FORCED CONVECTION AND PERFORMANCE EVALUATION IN A SQUARE DUCT HEAT EXCHANGER PLACED WITH WAVY THIN RIB - Boonloi, Amnart; Jedsadaratanachai, Withada (My University, 2020)
Simulated examinations on convective heat transfer and flow topology in a square duct heat exchanger placed with wavy thin rib (WTR) are presented. The influences of WTR heights, pitch distances and flow directions on flow and heat transfer characteristics are investigated for the laminar flow regime at the inlet condition (Re = 100 – 2000). The finite volume method (SIMPLE algorithm) is picked to analyze the numerical problem. The numerical validations; grid independence and verification of the smooth duct, are presented. The simulated results of the heat exchanger duct placed with WTR are reported in terms of flow and heat transfer visualizations. The relations of the Nu/Nu0, f/f0 and TEF with Re and P/H in the heat exchanger square duct inserted with WTR are also plotted. The numerical result reveals that the heat transfer and friction loss increase when augmenting the Reynolds number and WTR height. The optimum pitch spacing ratio may give the highest heat transfer rate and thermal performance.
Keywords: heat exchanger; heat transfer; numerical investigation; thermal performance; Wavy thin rib